2021
DOI: 10.1093/bjsopen/zraa038
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and health-related quality of life up to 2 years after oesophageal cancer surgery: nationwide population-based study

Abstract: Background Patients are at higher risk of suffering from psychological distress and reduced health-related quality of life (HRQoL) after oesophageal cancer surgery. This Swedish nationwide population-based longitudinal study aimed to evaluate the association between psychological distress and HRQoL up to 2 years after oesophageal cancer surgery. Methods The study included patients with oesophageal cancer who had survived for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
(8 reference statements)
0
17
0
Order By: Relevance
“…Data for the present study were drawn from a prospective, ongoing, Swedish nationwide, and population-based cohort study entitled Oesophageal Surgery on Cancer patients-Adaptation and Recovery (OSCAR). Details of the OSCAR study have been described elsewhere [26,27]. In brief, all 1-year survivors without cognitive impairment undergoing esophagectomy for cancer in Sweden from January 1, 2013, and onwards are invited (approximate response rate 66%) [26].…”
Section: Methodsmentioning
confidence: 99%
“…Data for the present study were drawn from a prospective, ongoing, Swedish nationwide, and population-based cohort study entitled Oesophageal Surgery on Cancer patients-Adaptation and Recovery (OSCAR). Details of the OSCAR study have been described elsewhere [26,27]. In brief, all 1-year survivors without cognitive impairment undergoing esophagectomy for cancer in Sweden from January 1, 2013, and onwards are invited (approximate response rate 66%) [26].…”
Section: Methodsmentioning
confidence: 99%
“… 15 At two years post-oesophagectomy, eating difficulties and reluctance to eat in front of others has been associated with psychological distress. 23 In a recent cross-sectional cohort study on patient-reported outcomes post-oesophagectomy, long-term symptom burden is common in this patient group, with swallowing/conduit problems being one of the six main problems reported. 24 Ten years post-operatively, swallowing difficulties persist for half of survivors.…”
Section: Introductionmentioning
confidence: 93%
“…One-year post-oesophagectomy, almost half of survivors’ report eating restrictions and other symptoms include dry mouth, taste problems, difficulty swallowing saliva and choking 15. At two years post-oesophagectomy, eating difficulties and reluctance to eat in front of others has been associated with psychological distress 23. In a recent cross-sectional cohort study on patient-reported outcomes post-oesophagectomy, long-term symptom burden is common in this patient group, with swallowing/conduit problems being one of the six main problems reported 24.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have highlighted that diagnosis and treatment are associated with signi cant and sustained levels of psychological morbidity (8,11). In oesophageal cancer patients, heightened levels of psychological distress have been associated with poorer health-related quality of life outcomes up to two years after surgery (12) and in gastric cancer patients, signi cantly higher incidence of depressive disorders have been identi ed compared to their healthy matched cohort (13). Whilst these studies have identi ed that surviving oesophago-gastric cancer and its subsequent treatment can have some adverse consequences for psychosocial functioning, there is wider evidence to suggest that palliative care needs increase and quality of life deteriorates once cancer advances beyond a curative state (14).…”
Section: Pre-registrationmentioning
confidence: 99%